2020
DOI: 10.1371/journal.pone.0235691
|View full text |Cite
|
Sign up to set email alerts
|

A pilot study investigating the effects of voluntary exercise on capillary stalling and cerebral blood flow in the APP/PS1 mouse model of Alzheimer’s disease

Abstract: Exercise exerts a beneficial effect on the major pathological and clinical symptoms associated with Alzheimer's disease in humans and mouse models of the disease. While numerous mechanisms for such benefits from exercise have been proposed, a clear understanding of the causal links remains elusive. Recent studies also suggest that cerebral blood flow in the brain of both Alzheimer's patients and mouse models of the disease is decreased and that the cognitive symptoms can be improved when blood flow is restored… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 97 publications
0
19
1
Order By: Relevance
“…Such CBF reductions develop early in the pathogenesis of AD, when intervention would be most ideal ( 38 ). We previously showed that a small fraction of cortical capillaries is temporarily stalled at a four times higher rate in multiple mouse models of APP overexpression, as compared to WT mice ( 37, 39, 40 ). Furthermore, we found that administering an antibody against a neutrophil specific protein, Ly6G, led to a ~64% reduction in the incidence of capillary stalling and a ~17% increase in CBF.…”
Section: Discussionmentioning
confidence: 97%
“…Such CBF reductions develop early in the pathogenesis of AD, when intervention would be most ideal ( 38 ). We previously showed that a small fraction of cortical capillaries is temporarily stalled at a four times higher rate in multiple mouse models of APP overexpression, as compared to WT mice ( 37, 39, 40 ). Furthermore, we found that administering an antibody against a neutrophil specific protein, Ly6G, led to a ~64% reduction in the incidence of capillary stalling and a ~17% increase in CBF.…”
Section: Discussionmentioning
confidence: 97%
“…Both interval and continued exercise decreased the levels of hippocampal Aβ40 and Aβ42 levels, reduced lipid peroxidation and enhanced antioxidant defenses [23]. However, free running did not alleviate microvascular dysfunction [31], while, in another study voluntary exercise increased tissue oxygenation, which supports the metabolic demand of neurons [30]. Moreover, voluntary physical exercise mitigated the neurodegenerative changes in the brain such as disintegration of the pyramidal layer structure, neuronal loss, severe pericellular edema, and accumulation of amyloid and cerebral amyloid angiopathy [21].…”
Section: Article Highlightsmentioning
confidence: 95%
“…Physical activity also influenced the brain already affected by plaques and tangles. For example, treadmill exercise prevented inflammatory events triggered by Aβ in mice hippocampus [29] and was associated with fewer cortical Aβ deposits [30], increased number of proliferating neuronal stem cells in the dentate gyrus, reduced hippocampal volume occupied by amyloid plaques [31], reversed the lipid peroxidation increase and restored the reduction in AChE activity [26], compared to sedentary controls. Both interval and continued exercise decreased the levels of hippocampal Aβ40 and Aβ42 levels, reduced lipid peroxidation and enhanced antioxidant defenses [23].…”
Section: Article Highlightsmentioning
confidence: 99%
“…After 5-minute habitation to the enclosure, the total number of wheel's rotation was recorded during one hour to assess animal's running capability. A Wireless USB Hub (DIG-807, Med Associates, Inc.) and Wheel Manager Software (SOF-860, Med Associates, Inc.) were used for data collection [48,49]. The wheel was cleaned with soap and water before each new user.…”
Section: Measurement Of Voluntary Running With Counting Wheelsmentioning
confidence: 99%